Strategi Pengembangan Pesantren Bali Bina Insani Di Tengah Masyarakat Multikultural - Ahmad Fauzi; Nurul Khalimah; Putri Khasanah; Alvi Ziyadatul Khoiriyah; Eko Sumadi (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Strategy for Development of the Bali Bina Insani Islamic Boarding School in the Middle of a Multicultural SocietyThis observe especially goals to explain the heritage of the established order of the Bali Bina Insani Islamic boarding school, as well as to provide an explanation for the efforts and strategies for developing the Bali Bina Insani Islamic boarding school in developing its Islamic education and maintaining its existence in a multicultural society. The studies method used on this study is a qualitative studies method with a case examine approach. Facts series techniques had been performed via interviews, observations, and documentation which were then examined the use of the triangulation approach and analyzed using the concept of Miles & Hubarman inside the form of facts reduction, facts presentation, conclusion drawing, and records verification. The consequences of the examine suggest that the tolerance created on the Bali Bina Insani Islamic boarding school is very strong so that it can become a special strategy in developing education at the Bali Bina Insani Islamic boarding school and is capable of be an effort to hold the existence of Islamic boarding schools that stand within the midst of a multicultural society with the general public being Hindu.Abstrak: Strategi Pengembangan Pesantren Bali Bina Insani di Tengah Masyarakat MultikulturalPenelitian ini secara spesifik bertujuan menjelaskan latar belakang berdirinya Pesantren Bali Bina Insani dan menjelasakan bagaimana upaya serta strategi pengembangan Pesantren Bali Bina Insani dalam menyebarkan pendidikan Islamnya serta mempertahankan eksistensinya di tengah rakyat multikultural. Penelitian ini memakai metode penelitian kualitatif melalui pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui tanya jawab, pengamatan di lapangan, serta dokumentasi yang kemudian diuji melalui metode triangulasi dan dianalisis memakai teorinya Miles & Huberman yang berupa reduksi data, penyajian data, penarikan konklusi, serta pembuktian data. Sehingga penelitian ini membuktikan bahwa toleransi pada Pesantren Bali Bina Insani sangat kuat sehingga bisa menjadi taktik khusus pada pengembangan pendidikan Islam Pesantren Bali Bina Insani serta bisa sebagai upaya mempertahankan keberadaan (eksistensi) pondok pesantren yang berdiri di tengah warga multikultural yang dominan beragama Hindu.